Upaya Penurunan Downtime pada Mesin Moulding di PT. X - Ardyanto, Marvin; Felecia, Felecia (Jurnal Titra, 2015)
PT. X is a company that processed log wood into timber products with size, type of wood, and the shape of the profile are produced depends on the buyerâs order. The company needs the process with a machine that can work continuously without any obstacle in order to meet the demand. Moulding machine in PT. X has downtime with an average 13,22% which the company want to reduce it. The main cause of downtime on the moulding machine is the changeover and breakdown. How to reduce changeover time is by using the method of Single Minute Exchange of Dies (SMED) and reduce frequency and time of the breakdown by making preventive maintenance schedule based on the MTTF value. The proposed improvements to reduce changeover time is doing some activities before the machine stops, making a new storage for tools and ring, and do the parallel changeover. The proposed improvements using the method SMED when applied can reduce changeover time with an average decrease in time estimation of 33,26%. Preventive maintenance schedule on the moulding machines based on the simulation results within a year can reduce downtime due to breakdown with an average of 57,55%.